2019
DOI: 10.1111/omi.12260
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates the pathogenic and inflammatory properties of Porphyromonas gingivalis

Abstract: Porphyromonas gingivalis has been strongly associated with chronic periodontitis, which affects tooth‐supporting tissues. This Gram‐negative anaerobic bacterium produces a repertoire of virulence factors that modulate tissue destruction directly or indirectly by the induction of inflammatory processes. The aim of this study was to investigate the effects of resveratrol, a major polyphenol found in grapes and wine, on the growth and virulence properties of P. gingivalis as well as on gingival keratinocyte tight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 85 publications
(114 reference statements)
1
22
0
Order By: Relevance
“…For example, they may disrupt cell membranes, inhibit nucleic acid metabolism, or disrupt synthesis of important components critical for bacterial cell survival such as proteins, nucleic acids, or cell walls. Several studies in the literature [42][43][44][45] have investigated the potential modes of action of polyphenols against various Gram positive and negative bacteria, such as S. aureus, E. coli, P. aeruginosa and P. gingivalis. These studies showed that the polyphenols act on the bacterial cell membranes, resulting in altered cell surface morphology, subsequent damage and increased cell permeability.…”
Section: Discussionmentioning
confidence: 99%
“…For example, they may disrupt cell membranes, inhibit nucleic acid metabolism, or disrupt synthesis of important components critical for bacterial cell survival such as proteins, nucleic acids, or cell walls. Several studies in the literature [42][43][44][45] have investigated the potential modes of action of polyphenols against various Gram positive and negative bacteria, such as S. aureus, E. coli, P. aeruginosa and P. gingivalis. These studies showed that the polyphenols act on the bacterial cell membranes, resulting in altered cell surface morphology, subsequent damage and increased cell permeability.…”
Section: Discussionmentioning
confidence: 99%
“…This process results in the production of mediators such as pro-inflammatory cytokines and nitric oxide in stimulated macrophage cells [ 26 ]. Since pro-inflammatory cytokines are recognized to play a vital role in cell signalling and systemic inflammation, the excessive production of pro-inflammatory cytokines may result in tissue destruction and the development of several pro-inflammatory processes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to investigate whether the addition of RV-HPβCD oral spray to oral hygiene procedures reduces plaque and gingivitis in children 2–5 years old, due to its potential for host modulation and antimicrobial activity [ 10 ]. RV alone exerts antibacterial effect against oral microbial pathogens involved in periodontal disease and dental caries, such as Porphyromonas gingivalis , Aggregatibacter actinomycetemcomitans [ 29 , 30 ] and Streptococcus mutans [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the remarkable pleiotropic activities (anti-inflammatory, anti-bacterial, anti-oxidant) of RV in the oral cavity [ 10 ]. It efficiently inhibits, not only the growth of Gram-negative periodontal pathogens [ 29 , 30 ], but also causes a decrease in oxidative burst capacity of neutrophils and in pro-inflammatory cytokines produced in the gingival tissues [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%